NASCIMENTO PRÉ-TERMO: problema de Saúde Pública sobre o qual muito se fala e pouco se pesquisa e se previne no Brasil - Marizélia Rodrigues Costa Ribeiro (Universidade Federal do Maranhão, 2010)
Public Health problems about which much is spoken and little is researched and prevented in Srazil Abstract: Preterm birth is a Public Health problem about which much is said in Obstetrics and Pediatrics services and little is researched and prevented considering this health problem in Brazil. This article debates the main reasons for preterm birth to be considered a Public Health problem and the main issues for establishing its rates and understanding how its determinants operate, in order that projects and programs about prevention may be effective and efficient. It is the main cause of neonatal and child mortality in the world. There are studies showing trends of increasing rates of preterm birth in Brazilian municipalities. It causes morbidities that may persist throughout life. There are limitations regarding: rate estimates, knowledge about how its determinants operate, cost to the families and for the State and prevention of preterm birth. Preterm birth is a complex consequence of causal courses. It is of most urgency to improve prenatal care for women at risk.